Follicular eruption with folliculotropic lymphocytic infiltrates associated with anti‐tumor necrosis factor alpha therapy: Report and study of 3 cases. (27th October 2019) - Avitan‐Hersh, Emily; Dias‐Polak, David; Ramon, Michal; Zaaroura, Hiba; Sahar, Dvora; Bergman, Reuven
Abstract: Background: We have encountered three cases of follicular eruptions with folliculotropic infiltrates of non‐atypical lymphocytes associated with anti‐tumor necrosis factor alpha (TNF‐α) therapy. Methods: Three patients aged 15 to 56 years treated with anti‐TNF‐α therapy (one with adalimumab, and two with infliximab) developed follicular eruptions characterized histopathologically by folliculotropic lymphocytic infiltrates. These were studied clinically, histopathologically, immunophenotypically, and molecularly. Results: All three cases were characterized histopathologically by folliculotropic cell infiltrates of non‐atypical T (CD3+) lymphocytes with variable follicular exocytosis. Marked reduction in CD7 staining and marked predominance of CD4+ cells over CD8+ cells were observed in 1 and 2 cases, respectively. T‐cell receptor (TCR) gene rearrangement studies were monoclonal in 1 case. Discontinuation of anti‐TNF‐α therapy in all three cases, with corticosteroid creams in 1 case, led to complete resolution. Rechallenge with adalimumab in 1 case resulted in exacerbation. Replacement of therapy with non‐anti‐TNF‐α biologic agents in 2 cases was not associated with recurrence. Conclusion: Follicular eruptions with folliculotropic lymphocytic infiltrates associated with anti‐TNF‐α therapy may show some immunophenotypical variations and/or monoclonal TCR gene rearrangements but lack sufficient cytomorphological features of folliculotropic MF. They may resolve with discontinuation of anti‐TNF‐α therapy.